Workload Analysis Using Full Time Equivalent Method To Optimize Employee Performance At Pt. Xyz - Nita Kanya (SEAN Institute, 2023)
XYZ is the only state-owned company engaged in the telecommunications sector in providing telecommunications services with the largest network in Indonesia. At PT. XYZ has a legal settlement unit where human workers are to help realize company goals. The purpose of this study was to find out how the workload of the legal settlement unit and its support units was and to find out the optimal number of workers at PT. XYZ. This study uses qualitative methods, in this study it does not test hypotheses, but only describes and analyzes the data. This study also uses the Full Time Equivalent method, which is a workload analysis method that measures the length of time it takes to complete work. Based on the results of research using the Full Time Equivalent method, it is known that there is an imbalance in the workload of the 8 units. Where there are 6 units with excessive workload including the Legal settlement unit, 3 proposed workers are needed, PT. XYZ regional 3 requires 7 proposed workers, PT. XYZ regional 4 requires 4 workers, PT. XYZ regional 5 requires 3 proposed workers, PT. XYZ regional 6 requires 2 proposed workers, and PT. XYZ regional 7 requires 2 proposed workers, while only 2 units have a normal workload, namely PT. XYZ regional 1 and 2. After making improvements by balancing the workload of other units that are excessive by adding the proposed workforce. The result is that the total workload on all units can be carried out by 42 workers.